Investigating the potential and feasibility of an offshore wind farm in the Northern Adriatic Sea. (1st September 2016) - Schweizer, Joerg; Antonini, Alessandro; Govoni, Laura; Gottardi, Guido; Archetti, Renata; Supino, Enrico; Berretta, Claudia; Casadei, Carlo; Ozzi, Claudia
Highlights: First feasibility study for an offshore wind farm in the Northern Adriatic Sea. Field wind and wave data collected at the site. Site-specific design of transition piece and foundation. Economical and technical feasibility applied to four different scenarios. Abstract: The use of offshore wind power is becoming increasingly important towards a sustainable growth worldwide. In Italy, as well as in other countries where wind energy is provided only by onshore plants, the interest in the deployment of offshore wind resources is rapidly growing, despite relatively modest average wind speeds, compared to typical wind conditions in the North Sea. Research efforts have, so far, addressed the exploration of the most promising locations, based on wind characteristics; however, more extended evidence of technical and economic feasibility is now needed to raise awareness in the decision makers and secure to this source of renewable energy a proper role in the future energy policies. Within such a context, the paper presents the first feasibility study for the development of an offshore wind farm off the coast of Rimini, in the Northern Adriatic Sea. The study is based on an anemometric campaign started at the site in 2008 to provide a statistical assessment of the wind characteristics and the related wind energy potential, and on a 10-year wave measurement record next to the area, together with a thorough analysis of the site geological and environmental characteristics. Environmental data are interpreted with a proper consideration of the extreme events distribution and relevant results are used to select the most appropriate commercially available wind turbine and to design the site-specific support structure. A comprehensive evaluation of the investment costs and revenues is then carried out with reference to two wind farm layouts (a first smaller, constituted of 15 elements, and another one, featuring up to 60 elements) and in relation to two different scenarios, conservative and comparatively more realistic. Results of the study clearly show that the Northern Adriatic Sea is potentially suitable for the development of a large wind farm and should encourage investments on more advanced experimental campaigns and related studies in order to prove the feasibility of innovative technological solutions that would substantially increase the profitability of such installation.